Cartilage Chips in Rhinoplasty - Apaydin, Fazil; Fernández-Pellón Garcia, Rodrigo Fortunato; Sahin, Fetih Furkan; Rahavi-Ezabadi, Sara (Facial Plastic Surgery, 2022)
Objective This study reveals that the cartilage chips can be a good solution for camouflage and augmentation in rhinoplasty.Methods In this study, 64 patients who had undergone rhinoplasty from 2014 to 2019 were retrospectively studied. The average age was 31. Forty-nine patients had primary and 15 revision rhinoplasties. Cartilage chips were cut into less than 0.5-mm thickness dimensions changing from 2 to 10 mm. They were used to fill deep radix, depressions at the key area, supratip area, around the grafts to prevent their visibility at the tip. In addition, they were used in the fascia for augmentation. The cartilage chips were sculpted from the septal cartilage in 47, rib in 16, and ear cartilage in one case.Results They were applied on the radix in 25, middle vault in 37, supratip area in 32, and on the tip in 12 cases. In 30 cases, cartilage chips were mixed with cartilage dust for better fixation and camouflage. They were placed in the fascia in three cases for dorsal augmentation. Complications were seen in three cases in the form of irregularities.Conclusion Cartilage chips are found to be a powerful solution in terms of camouflage and augmentation.
Keywords: cartilage chips; camouflage; augmentation; rhinoplasty; revision rhinoplasty; radix depressions; nose